Design on-board data processing for double Langmuir probe on lean satellite. Issue 1 (April 2021) - Suryana, R; Tejumola, T W; Kim, S; Cho, M
Abstract: The explosive growth of lean satellites (small/micro/nano/pico) has positioned this class of satellites as a unique tool for space science missions. Langmuir probe is one of the most frequently used payloads to achieve space plasma measurement missions because of their low requirement in terms of system development, size, and relatively low power requirements to drive the mission. Double Langmuir probe can overcome the limitations of a single Langmuir probe measurement as reference ground in the satellite is not required. The limitation of data communication speed is one of the problems that always occur in the development of a multi-mission lean satellite. Data communication speed can be improved by using another system such as S-band or X-band, but those will be required for high power consumption. One of the solutions is the reduced size of the data by using on-board data processing on satellites. On-board data processing aims to improve data communication speed when sending DLP data to ground stations and how to determine plasma parameters. On-board data processing for a double Langmuir probe will be calculated electron temperature and electron density by using Raspberry PI zero. On-board data processing aims to reduce the size of data so that the time of transmission between satellite and ground stations will be shorter. On-board data processing can be a pragmatic solution because processed data only contains useful information according to user requirements.